2017
DOI: 10.1007/s00702-017-1679-x
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of methylphenidate on attention in Wistar rats treated with the neurotoxin N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine (DSP4)

Abstract: The aim of this study was to assess the effects of the neurotoxin N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine (DSP4) on attention in rats as measured using the 5-choice-serial-reaction-time task (5CSRTT) and to investigate whether methylphenidate has effects on DSP4-treated rats. Methylphenidate is a noradrenaline and dopamine reuptake inhibitor and commonly used in the pharmacological treatment of individuals with attention deficit/hyperactivity disorder (ADHD). Wistar rats were trained in the 5CSRTT and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
(149 reference statements)
1
0
0
Order By: Relevance
“…That AMPH and MPH did not affect accuracy is generally consistent with previous 5CSRTT studies in healthy rodents treated with comparable (low to moderate) doses of MPH (Navarra et al 2008;Milstein et al 2010;Fernando et al 2012;Pattij et al 2012;Hauser et al 2017) and AMPH (Cole and Robbins 1987;Harrison et al 1999;Van Gaalen et al 2006;Loos et al 2010;Balachandran et al 2018;Higgins et al 2020). Although a few studies have reported these drugs to improve accuracy during increased task demand and/or in low-attention rats (Koffarnus and Katz 2011;Robinson 2012;Caballero-Puntiverio et al 2017;Toschi et al 2021) as well as in high-impulsive rats (Caprioli et al 2015), we did not observe any effects on accuracy in LA rats.…”
Section: Effects Of Stimulant Drugs On Attention; Mph Versus Amphsupporting
confidence: 92%
“…That AMPH and MPH did not affect accuracy is generally consistent with previous 5CSRTT studies in healthy rodents treated with comparable (low to moderate) doses of MPH (Navarra et al 2008;Milstein et al 2010;Fernando et al 2012;Pattij et al 2012;Hauser et al 2017) and AMPH (Cole and Robbins 1987;Harrison et al 1999;Van Gaalen et al 2006;Loos et al 2010;Balachandran et al 2018;Higgins et al 2020). Although a few studies have reported these drugs to improve accuracy during increased task demand and/or in low-attention rats (Koffarnus and Katz 2011;Robinson 2012;Caballero-Puntiverio et al 2017;Toschi et al 2021) as well as in high-impulsive rats (Caprioli et al 2015), we did not observe any effects on accuracy in LA rats.…”
Section: Effects Of Stimulant Drugs On Attention; Mph Versus Amphsupporting
confidence: 92%